EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION ON PERFORMANCE OF MEDICAL RECORD EMPLOYEES IN GRANDMED HOSPITAL LUBUK PAKAM - Monica Helen; Windi Anggreni Sitepu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Medical record service in hospitals has an importand thing in hospital service. Medical records are files containing record and documents about patients that contain identity, examination, treatment and other medical actions. This reserce aims to see the effect of work discipline and work motivation on the performance of medical record employees at Grandmed Hospital Lubuk Pakam. Work discipline is the obedience of an employees in carrying out his duties in accordance with predetermined regulations. Work motivation is an encouragement that grows from within person, both from within and from outside oneself in doing work with high enthousiasm which aims to get work results so that the desired satisfaction is achieved. The Subejct of this study were all of employess at medical record at Grandmed hospital Lubuk Pakam as many as 10 employess. The type of reserch used was explanatory survey. Collecting data using questionnaires and interview. Analysis of data using statistical test of Rank Spearman. Based on these results of research by compairing rho count value with rho table value (?= 0,05) and the result of this reserch value 0,370, show that is significant relationship between work discipline and work motivation (0,79>0,370). Conclution in this reserch is a effect between work disciplinr and work motivation on the performance of medical record employees at Grandmed Hospital Lubuk Pakam.